2018
DOI: 10.1007/s10096-018-3354-z
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus: epidemiology, clinical aspects, diagnosis, and control of infection

Abstract: Zika virus (ZIKV) is an emerging pathogen of huge public health significance to human beings. Although majority of infections are benign with self-limiting symptoms, the recent outbreak has established an association with the increased incidence of some congenital anomalies such as microcephaly. In other words, due to the large extent of the virus and mosquito vectors, the infection has become a thoughtful health problem for human societies, though now, there are no antiviral therapies or vaccines against this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 107 publications
0
13
0
2
Order By: Relevance
“…In addition, Zika virus (ZIKV), one of the emerging viruses in the world, is a member of the virus family Flaviviridae 46 . Since its discovery in Uganda in 1947, ZIKV has continued to expand its geographic range and threatens to devastate the population 47 . Myhrvold et al reported a specific and sensitive method for in vitro diagnosis of the dengue virus (DENV) and ZIKV, directly 41 .…”
Section: Crispr/cas–based In Vitro Diagnosticsmentioning
confidence: 99%
“…In addition, Zika virus (ZIKV), one of the emerging viruses in the world, is a member of the virus family Flaviviridae 46 . Since its discovery in Uganda in 1947, ZIKV has continued to expand its geographic range and threatens to devastate the population 47 . Myhrvold et al reported a specific and sensitive method for in vitro diagnosis of the dengue virus (DENV) and ZIKV, directly 41 .…”
Section: Crispr/cas–based In Vitro Diagnosticsmentioning
confidence: 99%
“…ZIKV was first isolated from rhesus monkey 766 in the Zika forest in Uganda in 1947 as part of a yellow fever surveillance study [13]. This was followed by the first recorded human infections in 1952 in Uganda and Tanzania [14][15][16]. There were 14 sporadic cases reported between the 1960s and 80s without serious consequences since the disease presented as a self-limiting febrile illness [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…This immune-mediated demyelinating neuropathy can rapidly evolve over a period of few days or more and can lead to paralysis or even death. [5][6][7] The initial symptoms of GBS include muscle weakness that starts from distal limbs which subsequently progresses to proximal limbs. [8] GBS may lead to respiratory failure requiring mechanical ventilation over 15% of cases.…”
Section: Guillain-barré Syndrome: Symptoms and Causesmentioning
confidence: 99%
“…[15,16] Infection by Campylobacter jejuni is identified as the most common inciting event although other agents such as herpes simplex virus (HSV), cytomegalovirus (CMV), Epstein-Barr virus (EBV), Zika virus (ZIKV), Mycoplasma pneumoniae, Haemophilus influenza, and influenza have been reported. [7,[17][18][19][20][21][22] Vaccination to influenza has been implicated in GBS, although the evidence for this link is controversial. [23]…”
Section: Guillain-barré Syndrome: Symptoms and Causesmentioning
confidence: 99%